Second-line and salvage therapies for steroid-refractory acute graft-versus-host disease: an integrated synthesis of current evidence and clinical sequencing - Julieta Zuluaga; Alexandros Kanelopoulos; Emmanouil Nikolousis (Current Opinion in Hematology, 2026)
Purpose of review Acute graft-versus-host disease (aGVHD) remains a principal driver of nonrelapse mortality after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Fifty percent of patients fail to achieve durable responses to first-line corticosteroids, defining steroid-refractory aGVHD (SR-aGVHD) and limited long-term survival. The Janus kinase 1/2 (JAK1/2) inhibitor ruxolitinib became the standard second-line therapy. Nevertheless, primary resistance and secondary loss of response continue to leave a substantial proportion of patients without effective treatment. Recent findings This review synthesizes evidence available up to June 2026 on second-line and salvage options that complement or follow ruxolitinib, including mesenchymal stromal cells, extracorporeal photopheresis administered alone or in combination with ruxolitinib, mammalian target of rapamycin (mTOR) inhibitors with or without interleukin-2 receptor antagonists (IL-2RAs), the humanized anti-CD25 monoclonal antibody xenopax, antithymocyte globulin as salvage, and investigational agents. We examine 2025 four-RCT meta-analysis supporting mesencymal stem cells (MSCs), the 2025 conditional approval by the Chinese NMPA of umbilical cord-derived MSC product for SR-aGVHD, the REACH2 long-term data, and biomarker-guided risk stratification using suppression of tumorigenicity 2 and regenerating islet-derived 3-alpha (REG3α). Summary We propose an evidence-based clinical sequencing algorithm that integrates ruxolitinib, MSCs, extracorporeal photopheresis (ECP), mTOR-targeted salvage, ATG, and clinical trial enrollment and supportive-care priorities, including infectious prophylaxis and organ-specific management.